2016
DOI: 10.1080/00128775.2016.1254564
|View full text |Cite
|
Sign up to set email alerts
|

Gross Exports Versus Value-Added Exports: Determinants and Policy Implications for Manufacturing Sectors in Selected CEE Countries

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 37 publications
(41 reference statements)
0
17
0
1
Order By: Relevance
“…Recent studies have further extended this initial model (Allard et al, 2016; Amador & Cabral, 2014; Guilhoto et al, 2015; Kowalski & Lopez‐Gonzalez, 2016; Olczyk & Kordalska, 2017; Yücer et al, 2014). From these extensions and based on the graphical analyses, we assume three different linear empirical models, one for the global participation model (Equation 2), one for upstream participation in a GVC (Equation 3) and one for downstream participation in the GVC (Equation 4).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent studies have further extended this initial model (Allard et al, 2016; Amador & Cabral, 2014; Guilhoto et al, 2015; Kowalski & Lopez‐Gonzalez, 2016; Olczyk & Kordalska, 2017; Yücer et al, 2014). From these extensions and based on the graphical analyses, we assume three different linear empirical models, one for the global participation model (Equation 2), one for upstream participation in a GVC (Equation 3) and one for downstream participation in the GVC (Equation 4).…”
Section: Methodsmentioning
confidence: 98%
“…Recent researches add supplementary explanatory variables (Allard et al, 2016; Amador & Cabral, 2014; Guilhoto et al, 2015; Kowalski & Lopez‐Gonzalez, 2016; Olczyk & Kordalska, 2017; Yücer et al, 2014) like the level of industrialization measured by industrial value‐added as a percentage of GDP ( INDUSVA it ), market size captured by population ( POPULATION it ), and technology measured here by internet access ( INTERNET it ). The effects of those variables are supposed to be positive whatever the position within the value chain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CEECs' exports to Germany and of their imports from Germany indicate different positions of the CEECs on the one hand and of Germany on the other hand in GVCs. Olczyk -Kordalska (2017) showed that the CEECs "do not occupy a favourable position in GVCs. Probably, they are positioned in the middle part of the GVCs".…”
Section: Bilateral Trade Of the Ceecs With Germany In Value Added Termsmentioning
confidence: 99%
“…The pre-production (product concept, design, R&D) and post-production (sales and marketing, aftersales services) stages create relatively considerable value added. Olczyk -Kordalska (2017) discovered also that during 1995-2011 the CEECs "were not able to go up into the higher stages of GVCs in which more value is generated". However, certain authors note that some sectors, e.g.…”
Section: Bilateral Trade Of the Ceecs With Germany In Value Added Termsmentioning
confidence: 99%